MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA TUGU BANDUNG, KECAMATAN KABANDUNGAN, KABUPATEN SUKABUMI - Kusumaningrum, Ria; Nurhasan, Abdul Khodir; Khapid, Muhamad (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2025)
This community service aims to design an appropriate Sharia Microfinance Institution (LKMS) for the Tugu Bandung Community Village, Kabandungan District, Sukabumi Regency. Using a qualitative approach, this community service collects data through in-depth interviews and participant observation to understand the financial needs of the community and the potential of local businesses. The results of community service show that there is an urgent need for financial access that is in accordance with sharia principles, especially in financing micro and small businesses. This research proposes the development of mudharabah and musyarakah- based financing products, as well as financial education programs to increase public literacy regarding sharia financial principles. This design is expected to not only meet the financial needs of the community, but also encourage local economic growth and empower community members. The findings from this research provide an important contribution to the development of LKMS models in rural areas, with a focus on sharia values and economic studies. Apart from that, the results of this community service can be used as a reference for further research in the field of sharia microfinance in Indonesia.